Optimizing HIV testing services in sub-Saharan Africa: Cost and performance of verification testing with HIV self-tests and tests for triage - Eaton,J; Terris-Prestholt,F; Cambiano,V; Sands,A; Baggaley,R; Hatzold,K; Corbett,E; Kalua,T; Jahn,A; Johnson,CC (Journal of the International AIDS Society, 2019)
Introduction:Strategies employinga single rapid diagnostic test (RDT) such as HIV self-testing (HIVST)or ‘test for triage’ (T4T)areproposed to increase HIV testing programme impact.Current guidelines recommend serial testing with two or three RDTs for HIV diagnosis, followed by retestingwith the same algorithmto verify HIV-positive statusbefore anti-retroviral therapy (ART) initiation. We investigated whether clientspresenting to HTS following a single reactive RDTmust undergo thediagnostic algorithm twice to diagnose and verify HIV-positive status, or whether a diagnosis with the setting-specific algorithm is adequate for ART initiation.Methods: We calculated (1)expected number of false-positive (FP) misclassifications per 10,000 HIV negative persons tested,(2)positive predictive value (PPV) of the overall HIV testingstrategy compared to WHO recommended PPV ≥99%, and (3) expected cost per FPmisclassified person identified by additional verification testingin a typical low-/middle-income setting, compared to the expected lifetime ART cost of $3000. Scenarios considered were: 10% prevalence using two serial RDTsfor diagnosis,1% prevalence using three serial RDTs,and calibrationusing programmatic data from Malawi in 2017where theproportion of people testing HIV positive in facilities was 4%. Results: In the 10% HIV prevalence settingwith a triage test, the expected number ofFP misclassifications was0.86 per 10,000 tested without verification testing and the PPV was 99.9%. In the 1% prevalence setting, expected FP misclassifications were 0.19 with 99.8% PPV, and in the Malawi 2017 calibrated setting the expected misclassifications were 0.08 with 99.98% PPV. The cost per FP identified by verification testing was $5,879, $3,770, and $24,259, respectively. Results were sensitive to assumptions about accuracy of self-reported reactive results and whether reactive triage test results influenced biased interpretation of subsequent RDT results by the HTS provid